Morphology and Features of Seeds of Different Species of Dry Deciduous Forest of Malwa Plateau Region - Singh, Jitendra; Chauhan, P. S.; kavita, A. (Indian Forester, 2012)
By and large, the seeds collected from the dry deciduous forests of the ’Malwa’ plateau region were medium to large in shape and mostly brown in colour. The majority of seeds manifested recalcitrant nature. Ripening of the seeds was mostly during summer months.